CONDITIONS OF FORMATION OF CREATIVE ACTIVITY OF STUDENTS BY MEANS OF INFORMATION – COMMUNICATION TECHNOLOGIES - Shlat, Natalia; Borisov, Boris; Eyliseyeva, Natalia; Shakirova, Nadezhda (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
The article deals with the problem of formation of creative activity among students in the process of using information and communication technologies (ICT) in the educational process of a higher educational establishment: features, prospects and conditions for effective formation of creative activity. The article describes an empirical study of the current level of formation of students' creative activity, gives examples of creative tasks developed by using ICT and recommendations for optimizing of the process of forming students' creative activity by means of ICT tools.